Evaluation of phosphate fertilizers for the stabilization of cadmium in highly contaminated soils - Thawornchaisit, Usarat; Polprasert, Chongrak (My University, 2009)
The efficiency of three phosphate fertilizers including triple superphosphate (TSP), diammonium phosphate (DAP), and phosphate rock (PR) as stabilizing agents of cadmium-contaminated soils has been assessed in this study. Two types of assessment criteria, (a) the reduction of leachable cadmium concentration; and (b) the changes in Cd association with specific operational soil fraction based on the sequential extraction data, are used in the evaluation of stabilization performance of each fertilizer. Results of the study showed that after the 60-day stabilization, the leachable concentrations of Cd in PR-, DAP- and TSP- treated soils reduced from 306 mg/kg (the control) to 140, 34, and 12 mg/kg with the stabilization efficiency as TSP>DAP>PR. Results from the assessment of Cd speciation via sequential extraction procedure revealed that the soluble-exchangeable fraction and the surface adsorption fraction of Cd in the soils treated with PO4 fertilizers, especially with TSP, have been reduced considerably. In addition, it is found that the reduction was correspondingly related with the increase of more stable forms of cadmium: the metal bound to manganese oxides and the metal bound to crystalline iron oxides. Treatment efficiency increased as the phosphate dose (based on the molar ratio of PO4/Cd) increased. In addition, it was observed that stabilization was most effective when using the molar ratio of PO4/Cd at 2:1 and at least 21-day and 28-day stabilization time for TSP and DAP, respectively. © 2008.
Keywords: Cadmium; Contaminated soils; Fertilizers; Heavy metals; Immobilization